2010
DOI: 10.1186/1753-6561-4-s2-p40
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcoma contains a subpopulation of cancer stem-like cells that are highly resistant to radiotherapy

Abstract: The cancer stem cell (CSC) theory states that tumors contain a subset of cells responsible for tumor initiation and growth and recurrence after treatments. We aimed to identify the presence of putative CSCs in a human MNNG/HOS osteosarcoma cell line and investigate their role in response to radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recent studies performed in our laboratory have identified a subset of cells with stem-like properties in OS that is relatively resistant to conventional chemotherapeutic agents and to ionizing radiation [8,9]. In this work we aim to identify the molecular mechanisms underlying the drug resistance phenotype exhibited by CSCs.…”
Section: Goalsmentioning
confidence: 99%
“…Recent studies performed in our laboratory have identified a subset of cells with stem-like properties in OS that is relatively resistant to conventional chemotherapeutic agents and to ionizing radiation [8,9]. In this work we aim to identify the molecular mechanisms underlying the drug resistance phenotype exhibited by CSCs.…”
Section: Goalsmentioning
confidence: 99%